Pre Clinic Grade and Clinic Periods Effect on Progress Test of UNISMA Medical Profession Students - Ariani Ratri Dewi (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Introduction: Pre clinic grade point is often seen as predictor of good performance in professional education whose short term goal is to pass national examination which command progress test to evaluate the preparation. Purpose: To know the effect of pre clinic grade point and clinical study periods in progress test result of medical profession students. Methods: 135 students of medical profession programme completed computer based progress test of 200 national standardized questions in 200 minutes using siPENA software. Progress test result then analysed based on how long they have been studied and their pre clinic grade point using ANOVA – Tukey HSD and Pearson correlation in SPSS for Windows ver 19 Results: Although students with pre clinic grade 2,50-2,74 have lower progress test result, but it’s not statistically significant (p>0,05). The same happen in clinic study periods with the longer the students in their clinical rotation, the better their result (p>0,05). The trends which showing better result in higher pre clinic grade point and time they spend in clinical rotation agrees with previous studies. Conclusion: Pre clinic grade point and clinic study periods has little to no effect on progress test result of medical profession students in UNISMA.